Comparison of linear, mixed integer and non-linear programming methods in energy system dispatch modelling - Ommen, Torben; Markussen, Wiebke Brix; Elmegaard, Brian (Energy (Oxford), 2014)
In the paper, three frequently used operation optimisation methods are examined with respect to their impact on operation management of the combined utility technologies for electric power and DH (district heating) of eastern Denmark. The investigation focusses on individual plant operation differences and differences between the solution found by each optimisation method. One of the investigated approaches utilises LP (linear programming) for optimisation, one uses LP with binary operation constraints, while the third approach uses NLP (non-linear programming). The LP model is used as a benchmark, as this type is frequently used, and has the lowest amount of constraints of the three. A comparison of the optimised operation of a number of units shows significant differences between the three methods. Compared to the reference, the use of binary integer variables, increases operation of selected units by 23%, while for a non-linear approach the increase can be higher than 39%. The results indicate a higher coherence between the two latter approaches, and that the MLP (mixed integer programming) optimisation is most appropriate from a viewpoint of accuracy and runtime. •Three operation optimisation methods for dispatch modelling are examined.•The investigation focusses on individual utility plant operation differences.•The comparison shows significant differences between the three algorithms.